The Role and Development of Technology-Intensive Suppliers in Resource-Based Economies: A Literature Review - Carlos Torres Fuchslocher (German Institute of Global and Area Studies (GIGA), 2007)
Although primary industries are important to developing countries, they have been largely unable to contribute to rapid growth. Systematically strengthening the development of local technology-intensive suppliers (t-suppliers), however, may contribute to both reinforcing the industrial base and supporting the competitiveness of primary production. Indeed, the development of t-suppliers has been common in those resource-based economies which achieved a high level of development (Scandinavia, Canada, Australia). This paper explores the role of t-suppliers in natural resource-based economies. It outlines a theoretical framework for the analysis of the factors which foster or constrain their development and defines areas for an effective promotion of t-suppliers. The proposed model of analysis distinguishes between factors influencing the development of t-suppliers on the level of the main industry (MI), the level of supplier firms or firm-level and the level of external determinants with special reference to industrial policy factors. – – Primärindustrien sind in vielen Entwicklungsländern von großer Bedeutung, haben in der Vergangenheit jedoch in der Regel nicht zu hohem Wachstum beitragen können. Eine systematische Förderung lokaler technologieintensiver Zulieferer kann nicht nur dazu verhelfen, die industrielle Basis des Landes zu stärken, sondern auch die Wettbewerbsfähigkeit der Rohstoffproduktion zu erhöhen. Tatsächlich stellt die Entwicklung von technologieintensiven Zulieferindustrien ein gemeinsames Charakteristikum der ressourcenbasierten hoch entwickelten Länder Skandinaviens (Finnland, Schweden, Norwegen) sowie Kanadas und Australiens dar. Der Autor dieser Studie untersucht die Rolle der technologieintensiven Zulieferer in ressourcenbasierten Entwicklungsländern. Er entwirft einen theoretischen Rahmen für die Analyse der Faktoren, die ihre Entwicklung fördern oder behindern und definiert Bereiche für eine effektive Förderung von technologieintensiven Zulieferindustrien. Das vorgeschlagene Analysemodell unterscheidet zwischen Faktoren auf der Ebene der Hauptindustrie, der Ebene der Zulieferindustrien oder Firmenebene und der Ebene externer Determinanten mit speziellem Bezug auf industriepolitische Faktoren.
Keywords: O14; Q22; R11; 330; technology-intensive suppliers; resource-based economies; developing countries; SME promotion; economic growth; Rohstoffwirtschaft; Lieferant; Technologie; Industrialisierung; Entwicklungsländer